The role of Ukrainian think tanks in shaping of public opinion on the European integration (on the example of Razumkov Centre and Gorshenin Institute) - Shkrobanets, Olena (Torun International Studies, 2015)
In this article the author has explored the role of Ukrainian think tanks, notably the Razumkov Center and Gorshenin Institute, in the formation of public opinion on the European integration policy of Ukraine during the period of 2007–2013. As a result of content analysis of these analytic institutes’ information materials it is concluded that the consolidated public opinion on the problem of European integration of Ukraine was not formed as Ukrainian citizens did not obtain from Ukrainian analytical structures complete, accurate and unambiguous information on this actual issue.